Effect of Aloe vera extract for reducing formaldehyde level in tuna fish for halal and thoyyib food - Subhan Rullyansyah; Fitrotin Azizah; Baterun Kunsah (Journal of halal product and research (JPHR), 2020)
This study aims to determine the effect of Aloe vera extract in reducing formaldehyde levels in tuna processed into "pindang" after being given Aloe vera extract. This type of research is experimental. The population in this study was boiled fish sold in the Sawotratap Market. This research was conducted at the Laboratory of Chemistry at the University of Muhammadiyah. Data were analyzed using analysis of variance at a significant level α = 0.05 followed by the Duncan test. The average formaldehyde concentration before being given Aloe vera extract at a concentration of 0% is equal to 23.7 mg / L, and the lowest formalin content in boiled fish with 100% treatment is equal to 5.6 mg / L. Aloe vera extract showed a significant decrease in formaldehyde levels in boiled fish (p <0.05). It can be concluded that the administration of Aloe vera extract is effective in reducing formaldehyde levels.